PROBABILITY OF MSMEs IN ACCESSING SHARIA FINANCING AT BMT FADHILLAH SENTOSA SUKOHARJO - Sekararum, Mellina; Pujiyono, Arif (Jurnal Syarikah : Jurnal Ekonomi Islam, 2024)
The current focus of the government is on Micro, Small, and Medium Enterprises (MSMEs) due to their significant role in Indonesia’s gross domestic product and employment. While MSMEs play a strategic role, many face challenges in terms of capital and limited access to formal financial institutions. Baitul Mall wat Tamwil (BMT) is one of the microfinance institutions that can provide a solution to the capital constraints of MSMEs by offering financial services. This research aims to analyze the opportunities for Sharia financing access for MSMEs in BMT. The data collection methods include interviews with BMT Fadhilah Sentosa in Sukoharjo Regency, distributing questionnaires and conducting interviews with MSME actors in Sukoharjo Regency, and studying relevant documentation to gather information and reports. The research method employed is Binary Logistic Regression, analyzing the impact of business turnover, business scale, business type, and business age on financing access. Data analysis is conducted using SPSS version 25. The logistic regression results indicate that business turnover and type of business are factors influencing MSMEs’ access to BMT financing. Higher business turnover increases financing access by 2.422 times. MSMEs engaged in trading businesses increase financing access by 3.848 times.